Performance Analysis of C-MRC Technique in DF Based Cooperative System with Co-Channel Interference - Aslan, Hayri; Ilhan, Haci; Ozdemir, Ozgur (IEEE, 2015)
We have investigated the performance analysis of DF (Decode-And-Forward) based cooperative system using cooperative MRC (C-MRC) at the destination with co-channel interference in Rayleigh fading channels. The performance of C-MRC is compared with maximal-ratio combining (MRC) using the effective Signal to Interference plus Noise Ratio (SINR) of the system. It is seen that performance of C-MRC technique is much better than that of MRC. The Monte Carlo simulations are provided to illustrate the effect of interference on the performance where interference channels are independent and identically distributed.
Keywords: DIVERSITY; Engineering